Application of N2-Fixing Cyanobacteria Nostoc sp. SO-A31 to Hydroponically Grown Water Spinach (Ipomoea aquatic L.) - Salamah, Andi; Fadilah, Nurrahmi; Khoiriyah, Istatik; Hendrayanti, Dian (AGRIVITA, Journal of Agricultural Science, 2019)
For this research, an application of cyanobacteria Nostoc sp. SO-A31 as a nitrogen source for the growth of water spinach (Ipomoea aquatica L.) was carried out using a modified Deep-Water Culture (DWC) hydroponic system, outdoors. A Hoagland medium was used for the growth medium, with the absence or presence of ammonium and nitrate as the nitrogen sources. A 0.7 g fresh weight biomass of 21-day-old Nostoc sp. SO-A31 was inoculated into the system. The four treatment media for this study were HA0 (Hoagland, ammonium free+inoculant), HN0 (Hoagland, nitrate free+inoculant), HA0N0 (Hoagland, ammonium free and nitrate free+inoculant), and HI (Hoagland with ammonium and nitrate +inoculant). AB-mix and complete Hoagland media were used as controls. The result showed that water spinach cultured on HA0 had good vegetative growth, as shown by the high yield of biomass, high number of leaves, high stem growth, and long roots. Inoculation of Nostoc sp. SO-A31 elongated the root of the water spinach plants in all treatments. The presence of Nostoc sp. SO-A31 in the complete Hoagland medium, though, caused chlorosis of the water spinach leaves. This study suggests that water spinach is a nitrate-dependent leafy vegetable.